Narratives of the Prophet’s Early Life in "Ṣaḥīḥ Al-Buḫārī": An Analytical Study of Qurʾānic References in "Sīra Nabawiyya" - Azmi, Ahmad Sanusi (Al-Bayān, 2017)
Research into early Muslim sources has demonstrated that some verses of the Qurʾān have been seen by Muslim scholars as containing direct references to the events of the Prophet’s early life. Modern scholars, however, have questioned the appropriateness and authority of these Qurʾānic references as being accurate sources of information for the Prophet’s biography. Since the ḥadīṯ are regarded as an authoritative exegetical tool for understanding the meaning of Qurʾānic verses, the ḥadīṯ and scholars’ views on the scripture and its relationship to the narratives of sīra nabawiyya must be undertaken. The objectives of this present study are to explore the narratives of the Prophet’s early life as found in Ṣaḥīḥ al-Buḫārī and analyse al-Buḫārī’s perspective on the role of ḥadīṯ as an exegetical tool for Qurʿānic references in sīra nabawiyya. The study is qualitative in nature, as it utilises both critical and analytical approaches for its methodology. The study suggests that al-Buḫārī employed innovative and novel approaches when presenting narratives of the Prophet’s early life. At certain places in his al-Ṣaḥīḥ, by adducing certain ḥadīṯ in detail, al-Buḫārī endeavours to convey one distinctive and irrevocable message to the reader.